Contribution to the appellative bases of Slovak hydronyms of the basin of Torysa - Chomová, Alexandra (Geographical names in physical space, 2016)
The paper is a partial study which refers to the processing of Slovak hydronymy within the Hydronymia Slovaciae project in mapping the names of water courses in the Eastern Slovakia. The research is carried out within the project Synchronic-diachronic aspects of the Hornad basin hydronymy (VEGA 1/0359/12). This article deals primarily with extralinguistic aspects of selected hydronyms. We selectively focus on the oldest documented hydronyms which are assumed to motivate other toponyms (for example settlements names). The contribution is based on an initial analysis of particular names, the evidence is acquired by extracts from maps and studies of materials relating mainly to the earliest, documented hydronyms from the Torysa basin. The Torysa is an important and the longest tributary river in the Hornád river basin. Its length is 129 kilometres. The oldest traces of settlement in the northern part of the Šariš stool are connected with this river. The aim of the article is to describe hydronyms which are motivated by the appellative base with the focus on the most common motivation – type of vegetation, landform and human activity associated with settlement (mainly inaccessible places). It also adds some comments on the influence of the Hungarian language, which allowed conserving some original speech sounds known in the oldest periods of Slovak language – for example the nasal consonant, the consonant g. These partial results of research in the study of the Torysa basin in Eastern Slovakia enrich the existing research and they also give opportunity to compare the appellative bases of names with the current findings of other Slovak outputs in the area of the hydronymia of Slovakia.